Contextualization of the Discipline of a Student Against the Teacher of the Perspective of the Qur'an Surah Al Hujurat Verses 1-3 - Hajjah Berlian Mustika; Muthoifin Muthoifin (Prosiding University Research Colloquium, 2022)
The purpose of this study is to find out the interpretation of the Qur'an in Surah al-Hujurat verses 1-3 according to the interpretation of Ibn Kathir and the contextualization of the adab of communicating a student to his teacher and the opinions of experts about the century of students to teachers today, so that it will be revealed it is easy to learn the wisdom of ethics in doing and talking to teachers. The method used in this study is a qualitative style, by describing and analyzing several literature books related to the research problem. The results of this study indicate that the contextualization and implementation of student ethics towards teachers is to improve the manners or ethics of a student, both in speaking or communicating and in treating the teacher well so that there are no deviant or contradictory traits that violate ethical teachings in Islam.